The American Foreign Policy towards Iran during Obama’s Presidency (2009-2017) - HAMOUMA, Chahrazad (My University, 2017)
Abstract The United States of America (U.S.A) presented itself as the worldwide power which interfered in the internal affairs of many countries such as Iran. Iran was considered as a threat to the international security due to its enrichment of the nuclear program, this made the US adopt several policies for limiting Iran’s nuclear capabilities. The current thesis presents a comprehensive investigation and analysis about the bilateral relationship between the US and Iran. The purpose of this study is to analyze the foreign policy adopted by Barack Obama towards Iran, examine the effectiveness and the outcomes of his policy, and compare his policy towards Iran with some previous president’s policies. This research uses the historical and analytical approaches for collecting and analyzing data. The study findings revealed that Obama adopted some strategies that focused primarily on imposing political and economic sanctions against Iran, but later on he shifted to the strategy of negotiations and diplomacy to resolve the conflict. In addition, the study indicated that Obama could elaborate a direct engagement between U.S and Iran that made the relation between the two countries better; thanks to the “Joint Comprehensive Plan of Action”, which legitimized the use of the nuclear weapons only in peaceful conditions. Moreover, the study revealed that the policy of Obama which relied also on the power of engagement and negotiations was better compared to Clinton and Bush’s policies; this is due to the fact that the previous policies were more confrontational.
Keywords: Key words: U.S.A, Iran, Obama, foreign policy, nuclear program, sanctions.